SOCIALISATION OF UMKM AS A FORM OF SERVICE FOR VILLAGE ECONOMIC INDEPENDENCE - Awaluddin Awaluddin; Al-Amin (Adiba Aisha Amira, 2024)
The socialisation of MSMEs as a form of community service aims to encourage village economic independence through increased capacity and participation of local communities. This initiative focuses on developing the knowledge and skills required to manage small and medium enterprises that have the potential to create jobs and increase the income of village communities. By utilising local potential and existing resources, the programme is expected to strengthen the village economic structure and reduce dependence on the central economy. The outcome of this socialisation is expected to create a sustainable business ecosystem and improve the overall welfare of the village community.